Pengaruh Kepuasan Pelanggan Terhadap Penggunaan Member Card di Pippo Coffee Roasters Kota Batam - Muhammad Hasib Bimantara; Rezki Alhamdi; Natal Olotua Sipayung; Tito Pratama (CV. ITTC INDONESIA, 2025)
Increasingly fierce competition in the coffee shop industry has driven businesses to understand customer behavior through loyalty programs, such as membership cards. A key factor influencing customers' decisions to utilize these cards is their satisfaction with the services and products offered. This study examines the impact of customer satisfaction on the usage of membership cards at Pippo Coffee Roasters in Batam City. Employing a quantitative approach with a survey method, data were collected via questionnaires distributed to 102 respondents selected through purposive sampling, specifically customers who hold membership cards. The research instrument underwent validity and reliability tests to ensure data accuracy and consistency. Data analysis utilized simple linear regression to assess the influence of customer satisfaction on membership card usage. The findings reveal that customer satisfaction has a positive and significant effect on membership card usage, with a coefficient of determination (R²) of 0.893, a regression coefficient of 0.896, and a t-test significance value of 0.000 (p < 0.05). This indicates that higher customer satisfaction levels correlate with increased membership card usage. Consequently, customer satisfaction plays a crucial role in encouraging participation in the loyalty program at Pippo Coffee Roasters. Consequently, elevated customer satisfaction with product quality, service, pricing, and ambiance positively correlates with increased membership card utilization.